Reasons for smoking and barriers to cessation among adults with serious mental illness: A qualitative study. Issue 6 (17th May 2019) - Keller‐Hamilton, Brittney; Moe, Aubrey M.; Breitborde, Nicholas J. K.; Lee, Angela; Ferketich, Amy K.
Abstract: Aims: Most research into reasons for smoking among adults with serious mental illness (SMI) has focused on reasons related to SMI symptoms. The current study reports reasons for smoking and barriers to cessation that are both related and unrelated to SMI symptoms among adults with SMI. Methods: Four focus groups were conducted among current smokers receiving outpatient care for a psychotic disorder in 2017 ( N = 24). Participants were asked why they currently smoke and their barriers to quitting smoking. Results: Smoking as a coping mechanism and to self‐medicate SMI symptoms were reasons for current smoking and barriers to cessation. Avoidance of other unhealthy behaviors, routine, and enjoyment emerged as reasons for smoking and barriers to cessation that were unrelated to mental illness. Conclusion: Consideration of factors that are both related and unrelated to SMI symptoms in smoking cessation interventions and brief cessation counseling may improve cessation success in this population.